Effect of La addition on the microstructure and martensitic transformation of Ni-Ti-La alloys. (March 2017) - Zhao, Chunwang; Li, Weiya; Zhao, Shilei; Jin, Yongjun; Meng, Xiaokai; Hou, Qingyu
Abstract: The effect of the addition of the rare earth element La on the microstructure and martensitic transformation behavior of Ni50 Ti50-x Lax (x = 0, 0.1, 0.3, 0.5, 0.7, 0.9) alloys was investigated experimentally. The microstructure of Ni-Ti-La alloys consists of the near-equiatomic TiNi matrix and LaNi precipitates. One-step martensitic transformation was observed in all Ni-Ti-La alloys. The martensitic transformation start temperatures decrease gradually with the increase of La fraction in Ni-Ti-La alloys. Highlights: Microstructure and martensitic transformation of Ni-Ti-La alloys were investigated experimentally. Ni-Ti-La alloys consist of the near-equiatomic TiNi matrix and LaNi precipitates. One-step martensitic transformation was observed in all Ni-Ti-La alloys. The martensitic transformation start temperature decreases gradually with the increase of La fraction.